CRIMINAL NEWS WRITING STRATEGY OF okemedan.com - Munajmi Ajri; Erwan Effendi (Journal Analytica Islamica, 2026)
The development of digital media encourages online media to present news quickly, up-to-date, and engagingly. However, this demand often faces the risk of violating journalistic ethics, particularly in crime reporting. Previous studies have focused more on the ethics of crime reporting in general, while discussions of crime news writing strategies in local digital media are still relatively limited. This study aims to analyze the crime news writing strategies on Okemedan.com and examine their compliance with journalistic principles and the reporting code of ethics. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations of reporting practices, and documentation of the crime news archives published by Okemedan.com. The key informant for this study is the managing editor of Okemedan.com, who has the authority in the selection, editing, and quality control processes of news. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. While data validity was strengthened through triangulation of sources, techniques, and time. The results of this study indicate that the crime news writing strategy on Okemedan.com emphasizes information verification, the use of official sources, the application of the 5W+1H elements, the selection of informative titles, and the avoidance of sensational language. The uniqueness of this study lies in the finding that Okemedan.com builds the appeal of crime news through a human interest approach and editorial control, rather than through the exploitation of violence or the suffering of victims. Thus, this study enriches the study of digital journalistic ethics by showing how local media can balance publication speed, reader needs, and social responsibility in crime reporting.